Pengaruh Penambahan Abu Tempurung Kelapa dan Silika Fume Terhadap Kuat Tekan Beton - Saputra, Ian Sugiawan; Sulfanita, Andi; Misbahuddin, Misbahuddin (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
Coconut shell ash and silica fume can enhance the strength and durability of concrete. Coconut shell ash, as an organic waste material, functions as a lightweight aggregate, while silica fume improves the bond between cement and aggregate, thereby increasing the overall durability of the concrete. This study aims to compare the compressive strength results and determine the optimal percentage of coconut shell ash and silica fume in both normal and mixed concrete at 28 days of curing, using an experimental method. The results showed that the compressive strength of normal concrete at 28 days was 26.33 MPa. After the addition of 2% coconut shell ash and 2% silica fume, the compressive strength increased significantly to 31.61 MPa, representing an improvement of 5.28 MPa. However, adding more than 2% coconut shell ash led to a decrease in compressive strength, with the lowest value of 22.36 MPa observed in the mixture containing 10% coconut shell ash and 2% silica fume. The optimal combination was found to be 2% coconut shell ash and 2% silica fume, yielding the highest compressive strength of 31.61 MPa. These findings suggest that organic waste such as coconut shell ash can serve as an environmentally friendly alternative in the construction industry, especially when combined with supplementary materials like silica fume.